Integration of Empiricism, Rationalism, and Postivism in Arabic Language Teaching: a Philosophy of Education Approach - Arif, Mochammad Saifudin; Yusuf, Kamal (JURNAL IJ-ATL, 2025)
Arabic language instruction often faces challenges due to its complex grammatical structure, diglossic nature, and the fragmented application of teaching philosophies. Traditionally, educational practices tend to favor isolated methods, either experiential, theoretical, or evaluative, leading to imbalanced learning outcomes and limited communicative competence. In response to this issue, this study investigates the integration of empiricism, rationalism, and positivism as a philosophical foundation for Arabic language teaching to develop a more comprehensive and balanced instructional model. Employing a qualitative case study approach, data were collected through classroom observations, interviews with Arabic language educators, and analysis of curriculum documents and instructional materials. The findings reveal that empiricist strategies such as contextualized role-plays and experiential learning enhance students’ functional language proficiency. Rationalist elements support conceptual mastery through structured grammar instruction and deductive reasoning, while positivist assessments provide objective measurement of learning outcomes through standardized evaluation tools. However, each paradigm, when applied in isolation, revealed limitations in supporting holistic language development. The study concludes that a philosophical integration of these three paradigms enriches Arabic language pedagogy by aligning practical, conceptual, and evaluative dimensions of instruction. This model contributes to the design of theoretically grounded, context-responsive Arabic teaching practices for more effective language acquisition.